Premarital Training as an Effort to Prevent Divorce Caused by Financial Problems - Aprilia, Weri; Tehupuring, Ronald (Jurnal Pengabdian Kepada Masyarakat, 2023)
During the COVID-19 pandemic, the divorce rate in Indonesia increased. The increase in divorce is caused by many factors including financial problems. In this case the financial factor does not always mean that the household has no income at all, but rather mistakes in managing household finances. The Research and Community Service Institute of Lepisi Higher Education held Pre-marital guidance at the GPIB Samaria Church, Tangerang city. The purpose of this activity is to provide basic financial knowledge to couples who are getting married so that they are scientifically prepared to manage young household finances and minimize the rate of divorce caused by financial problems.